The Effectiveness of the Window-Shopping Method in Teaching Vocabulary to Senior High School Students - Febrianti Falensia Gwasgwas; Nurteteng (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to determine the effectiveness of the Window-Shopping Bag method in improving students’ English vocabulary mastery. Conducted at SMAN 1 Fef, the research used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 7 tenth-grade students selected from an original population of 19 students, chosen based on consistent attendance and willingness to participate. All participants had very limited English proficiency and struggled to recognize even basic vocabulary. The research involved a pretest to assess initial vocabulary knowledge, followed by treatment sessions using the Window-Shopping Bag method, which engaged students in interactive, contextual learning through simulated shopping activities with labeled items and role-play. A posttest was administered to evaluate vocabulary improvement. The results showed a significant increase in scores, with the average pretest score at 42.86 and the posttest average rising to 72.16. The N-Gain score was 0.51, which falls into the medium category. According to the decision rule, since the N-Gain score is greater than 0.3, the null hypothesis is rejected, indicating that the Window-Shopping Bag method is effective in enhancing students’ vocabulary mastery. The method proved to be suitable for small groups with low proficiency, especially in remote areas with limited learning resources. It is recommended that future research involve a larger sample size and a longer period of implementation to better understand the method’s long-term impact.